2016
DOI: 10.1016/j.exer.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Primate neural retina upregulates IL-6 and IL-10 in response to a herpes simplex vector suggesting the presence of a pro-/anti-inflammatory axis

Abstract: Injection of herpes simplex virus vectors into the vitreous of primate eyes induces an acute, transient uveitis. The purpose of this study was to characterize innate immune responses of macaque neural retina tissue to the herpes simplex virus type 1-based gene delivery vector hrR3. PCR array analysis demonstrated the induction of the pro-inflammatory cytokine IL-6, as well as the anti-inflammatory cytokine IL-10, following hrR3 exposure. Secretion of IL-6 was detected by ELISA and cone photoreceptors and Mulle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…As an important supporting glial cell in the retina, Müller cell abnormal function has been linked to many retinal diseases (de Hoz et al, 2016; Sauter and Brandt, 2016; Wang et al, 2015b; Zhong et al, 2012). We found that ZIKV not only replicates productively in Müller cells but also induces a robust inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important supporting glial cell in the retina, Müller cell abnormal function has been linked to many retinal diseases (de Hoz et al, 2016; Sauter and Brandt, 2016; Wang et al, 2015b; Zhong et al, 2012). We found that ZIKV not only replicates productively in Müller cells but also induces a robust inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Müller cells form an architectural support structure across the whole retina and provide homeostatic and metabolic support to retinal neurons, which are assumedly carried out by astrocytes, oligodendrocytes and ependymal cells in other regions of the CNS (Newman and Reichenbach, 1996; Reichenbach and Bringmann, 2013). Under pathological conditions, Müller cells are activated and produce inflammatory cytokines and growth factors that lead to retinal inflammation, vascular leakage and neuronal degeneration in retinopathies including diabetic retinopathy, age-related macular degeneration and uveitis (de Hoz et al, 2016; Sauter and Brandt, 2016; Wang et al, 2015b; Zhong et al, 2012). Since ZIKV has been detected in cells located in the INL, including those with the morphology of Müller cells (Miner et al, 2016), here, we investigated the effects of ZIKV infection on primary mouse retinal Müller cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the TLRs were present in filamentous cells, suggesting they may be expressed by Muller cells, the predominant glial cell type in the retina. To confirm this, we utilized vimentin antibodies as a Muller cell marker (Bhatia et al, 2009; Sauter and Brandt, 2016) and performed double label IF with antibodies to TLRs 4-7. Staining with the anti-vimentin antibody identified a filamentous pattern of Muller cells extending throughout the retina (Fig 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Some TLRs were expressed in small, round cells in the INL, suggestive of amacrine cell morphology (Fig 3). We performed double label IF with anti-calretinin antibodies, which label AII amacrine cells (de Souza et al, 2016; Kolb et al, 2002; Mills and Massey, 1999; Sauter and Brandt, 2016), and antibodies to TLRs 4-7 to determine if TLRs were expressed by calretinin positive amacrine cells. The staining pattern of the anti-TLR6 antibody clearly indicated TLR6 positive round cells in the INL (Fig 7A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation